Botulinum toxin type A injections for treating neurogenic detrusor overactivity combined with low-compliance bladder in patients with spinal cord lesions - Jakkrit Klaphajone (2018)
Objective: To evaluate botulinum toxin type A (BTX-A) for treating neurogenic detrusor overactivity in patients with spinal cord lesions, including those with abnormally low bladder compliance. Design: Nonrandomized, before-after trial (9-mo follow-up). Setting: Hospitalized care. Participants: Ten patients with high detrusor contraction pressure and/or poor response to oxyphencyclimine with incontinence selected as a consecutive sample. Intervention: BTX-A (Botox; 300U) was injected into the detrusor muscle. Main Outcome Measures: Urinary continence, functional bladder capacity, bladder compliance, detrusor contraction pressure, and volume at first reflex voiding. Measurements were taken before and 6, 16, and 36 weeks posttreatment. Results: Six weeks after treatment, complete continence was restored in 7 patients without oxyphencyclimine. Mean functional bladder capacity (P=.008), compliance (P=.012), and reflex volume (P=.045) significantly increased, whereas maximal detrusor contraction pressure significantly decreased (P<.001). Urodynamic variables remained significantly improved at 16 weeks, but values were returning toward baseline levels by 36 weeks. The procedure was generally uneventful, without any serious side effects. Conclusions: BTX-A injections are an effective, well-tolerated treatment for neurogenic detrusor overactivity in patients with spinal cord lesions, even in patients with abnormally low bladder compliance. Patients may require repeat injections after 16 weeks to remain continent. © 2005 by the American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation.